Análise Comparativa dos Artigos de Filmes Indicados ao Oscar em Três Versões da Wikipédia - Pereira, Cecília Junqueira V. M.; Vasconcelos, Marisa Affonso; Silva, Ana Paula Couto da (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2024: Anais Estendidos do XXX Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2024.244399, 2024)
This work analyzes the differences in how Oscar-nominated films in the ‘Best Picture’ category are addressed in the English, Spanish and Portuguese versions on Wikipedia. Using text and graph analysis techniques, the connectivity and semantics of the articles in these languages were investigated, revealing that each language highlights different aspects of the films, reflecting the cultural and linguistic priorities of their respective communities.